Metamorfosis Gerakan Sosial Keagamaan: Antara Polemik, Desiminasi, Ortodoksi, dan Penerimaan terhadap Ideologi Lembaga Dakwah Islam Indonesia (LDII) - Limas Dodi (AL-TAHRIR, 2017)
Abstract: The Islamic Da'wah Institution of Indonesia (LDII) is connoted as the successor of Islamic Jamaah, thus it is labeled as heretical by certain parties. Even though there are many indications that lead to such perceptions. In fact, LDII is an organization formed by a New Era Government that is assigned to guard the deviation of Islamic teachings by Islamic Jamaah. This paper is intended to analize how far the metamorphosis (in the sense of releasing its past heretic, and its use of new paradigm) of LDII as religious social movement was influenced by Islamic Jamaah, that is between polemics, dissemination, orthodoxy, and the acceptance of its Ideology. Historical and cultural attachments of LDII to Islamic Jamaah lead to other religious groups to still insist on their decision of LDII doctrinal apostasy. The social movement depict that movement emerges and last from various forms and patterns. There are two patterns that influence State-oriented Islamic movement and society-oriented Islamic movement. It appears in two patterns: Everyday life-based and Inward-oriented contemplative movements. The dynamics and strategies of the LDII with government bureaucracies or other religious groups are relationships to position themselves as parallel groups as orthodox groups.الملخص: إن هيئة الدعوة الإسلامية الإندونيسية (LDII) تفهم بأنها الهيئة التي تواصل فكرة "إسلام جماعة"، فتعتبر بأنها جماعة منحرفة في نظر بعض الناس. وإن كان هناك أمارات تشير إلى ذلك الافتراض. ولكن الحقيقة أن هيئة الدعوة الإسلامية الإندونيسية هي هيئة أسسها نظام الحكم "العهد الجديد" (ORDE BARU) والتي مهمتها هي إصلاح انحرافات  "إسلام جماعة". وهذه المقالة تعالج مدى التغيرات (بمعنى: الانسلاخ من التقاليد القديمة التي تعتبر ضالة، ثم تسلك مسلك مفاهيم جديدة). والحركة الاجتماعية من هيئة الدعوة الإسلامية الإندونيسية (LDII) تؤثر فيها "إسلام جماعة"، ما بين جدال، ونشر، وأورثوذكسي، وقبول إيديولوجيتها. وتسبب العلاقة التاريخية والطبيعية بين هيئة الدعوة الإسلامية الإندونيسية (LDII) و"إسلام جماعة" أن الجماعات الدينية الأخرى مازالت تتمسك بقرار أن تعاليم هيئة الدعوة الإسلامية الإندونيسية (LDII) منحرفة وضالة.  والحركة الاجتماعية تصور لنا بأن الحركة تظهر وتدوم على عدة صور وأنماط، وهناك نمطان مؤثران: الحركة الإسلامية ذات توجه الدولة، والحركة الإسلامية ذات توجه الأمة. وتظهران على نمطين: 1. على أساس الحياة اليومية، و2. الحركة الداخلية الوجهة والتأملية. وحركات واستراتيجية هيئة الدعوة الإسلامية الإندونيسية (LDII) نحو الحكومة والجماعات الدينية الأخرى تعتبر محاولة لإظهار كيانها كجماعة ذات مكانة متساوية مع الجماعات القديمة.Abstrak: Lembaga Dakwah Islam Indonesia (LDII) dikonotasikan sebagai penerus dari perjuangan pemikiran Islam Jamaah, sehingga muncul labeling sesat oleh pihak-pihak tertentu. Meskipun banyak indikasi yang mengarahkan persepsi demikian, namun pada hakikatnya LDII merupakan suatu organisasi bentukan pemerintah Orde Baru yang ditugaskan untuk membenahi penyelewengan ajaran Islam yang dilakukan oleh kelompok Islam Jamaah. Tulisan ini berusaha untuk mengalisa sejauh mana metamorfosis (dalam arti; melepaskan dinamika masa lalu yang dianggap menyesatkan, dan kemudian memakai paradigma baru) gerakan sosial keagamaan LDII dipengaruhi oleh Islam Jamaah, antara polemik, desiminasi, ortodoksi, dan penerimaan terhadap Ideologi-nya. Keterikatan historis dan kultural LDII dengan Islam Jamaah menyebabkan kelompok keagamaan yang lain masih bersikukuh pada keputusan tentang kesesatan ajaran LDII. Gerakan sosial memberikan gambaran bahwa gerakan itu muncul dan langgeng dari berbagai macam bentuk dan pola-pola. Dalam hal ini terdapat 2 pola yang mempengaruhi: State-oriented Islamic movement dan society-oriented Islamic movement, ini muncul dalam dua pola. (1) Everyday life-based. (2) Inward-oriented contemplative movements. Dinamika dan strategi LDII dengan birokrasi pemerintahan ataupun kelompok keagamaan lainnya merupakan jalinan hubungan untuk memposisikan diri sebagai kelompok yang sejajar sebagai kelompok ortodoks.